2006
DOI: 10.1080/02791072.2006.10399827
|View full text |Cite
|
Sign up to set email alerts
|

Medical Use, Illicit Use and Diversion of Prescription Stimulant Medication

Abstract: The objective of this study was to examine the prevalence and factors associated with the illicit use of prescription stimulants and to assess the relationship between the medical and illicit use of prescription stimulants among undergraduate college students. A Web survey was self-administered by a random sample of 9,161 undergraduate students attending a large public midwestern university in the spring of 2003. A total of 8.1% reported lifetime illicit use of prescription stimulants and 5.4% reported past ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
244
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(273 citation statements)
references
References 50 publications
26
244
3
Order By: Relevance
“…10 , 11 , 14, 31 , 32 The studies vary with respect to age range of the samples, response rates, and the types of stimulants assessed; however, several interesting and consistent findings have emerged and have been replicated in the present study. Consistent with earlier studies, 13 , 32 we found that NPS appears to be generally infrequent and sporadic, with the majority of NPS+ individuals using them less than 12 times in their lives (85.3%). We also found that most students nonmedically use stimulants "purposefully" as an academic aid, that is, to help them study or cram for exams and write papers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…10 , 11 , 14, 31 , 32 The studies vary with respect to age range of the samples, response rates, and the types of stimulants assessed; however, several interesting and consistent findings have emerged and have been replicated in the present study. Consistent with earlier studies, 13 , 32 we found that NPS appears to be generally infrequent and sporadic, with the majority of NPS+ individuals using them less than 12 times in their lives (85.3%). We also found that most students nonmedically use stimulants "purposefully" as an academic aid, that is, to help them study or cram for exams and write papers.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that most students nonmedically use stimulants "purposefully" as an academic aid, that is, to help them study or cram for exams and write papers. 11, 31 We also found that the overwhelming majority of college students obtain prescription stimulants from friends, who either have or do not have a legitimate prescription.13 , 33 Lastly, consistent with McCabe et al, 32 we find it noteworthy that the students taking prescribed ADHD medication were outnumbered by lifetime nonmedical users of prescription stimulants, at a ratio of nearly five to one (45 vs. 218).In this study, the proportion of lifetime nonmedical users who cited recreational reasons for use (i.e., getting high or staying awake to party) was somewhat lower than in previous reports, which yielded estimates ranging from 19.3% to 70%.11 , 13 , 20 , 33 Similarly, inhalation of stimulants (14.2% of lifetime nonmedical users) was also less prevalent in this study than elsewhere. Although these differences may be partially attributable to methodological differences in the wording of questions, mode of administration, or geographic differences; it seems noteworthy that the college student samples in these prior studies have all been considerably older, whereas the present sample was restricted to firstyear students aged 17 to 20.…”
supporting
confidence: 74%
“…In humans, the use of psychostimulant treatment for ADHD may protect against the development of substance use disorders [12,49,52,91], especially if treatment is started in childhood [for a review, see 43]. Conversely, the present results may also suggest that use of psychostimulants by individuals without ADHD could increase the risk of substance abuse problems.…”
Section: Discussionmentioning
confidence: 85%
“…The METH metabolite (+)amphetamine (which produces subjective and physiological effects in humans and other species that are highly similar to METH) is marketed for ADHD therapy (Adderall®). Perhaps unsurprisingly, amphetamines formulated for oral therapeutic use are frequently diverted for recreational use (McCabe et al, 2006(McCabe et al, ,2004Upadhyaya et al, 2005;Wilens et al, 2006;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%